Benefits of motor imagery training on muscle strength - Lebon, F.; Collet, C.; Guillot, A. (The Journal of Strength and Conditioning Research, 2010)
It is well established that motor imagery (MI) improves motor performance and motor learning efficiently. Previous studies provided evidence that muscle strength may benefit from MI training, mainly when movements are under the control of large cortical areas in the primary motor cortex. The purpose of this experiment is to assess whether MI might improve upper and lower limbs' strength through an ecological approach and validation, with complex and multijoint exercises. Nine participants were included in the MI group and 10 in the control (CTRL) group. The 2 groups performed identical bench press and leg press exercises. The MI group was instructed to visualize and feel the correspondent contractions during the rest period, whereas the CTRL group carried out a neutral task. The maximal voluntary contraction (MVC) and the maximal number of repetitions (MR) using 80% of the pre-test MVC weight were measured. Although both MI and CTRL groups enhanced their strength through the training sessions, the leg press MVC was significantly higher in the MI group than in the CTRL group (p < 0.05). The interaction between the leg press MR and the group was marginally significant (p = 0.076). However, we did not find any difference between the MI and CTRL groups, both in the bench press MVC and MR. MI-related training may contribute to the improvement of lower limbs performance by enhancing the technical execution of the movement, and the individual intrinsic motivation. From an applied and practical perspective, we state that athletes may perform imagined muscles contractions, most especially during the rest periods of their physical training, to contribute to the enhancement of concentric strength.